2014
DOI: 10.1093/mnras/stu2019
|View full text |Cite
|
Sign up to set email alerts
|

The ATLAS3D project – XXIX. The new look of early-type galaxies and surrounding fields disclosed by extremely deep optical images

Abstract: Galactic archeology based on star counts is instrumental to reconstruct the past mass assembly of Local Group galaxies. The development of new observing techniques and data-reduction, coupled with the use of sensitive large field of view cameras, now allows us to pursue this technique in more distant galaxies exploiting their diffuse low surface brightness (LSB) light. As part of the ATLAS 3D project, we have obtained with the MegaCam camera at the Canada-France Hawaii Telescope extremely deep, multi-band, ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
175
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(186 citation statements)
references
References 81 publications
(82 reference statements)
5
175
0
Order By: Relevance
“…Aside from prominent individual stellar streams (e.g., [32,33]), the characterization of stellar halos has been very challenging owing to their extremely low surface brightnesses >30 V-band mag/arcsec 2 . Recent deep diffuse light imaging has permitted detection of relatively massive halos (e.g., [34][35][36]). In parallel, studies of resolved red giant branch (RGB) stars in the outskirts of nearby galaxies reach fainter equivalent surface brightness limits and give estimates of both stellar halo masses and typical metallicities [7,8,[37][38][39][40][41].…”
Section: Stellar Halos Measure Merger Historymentioning
confidence: 99%
“…Aside from prominent individual stellar streams (e.g., [32,33]), the characterization of stellar halos has been very challenging owing to their extremely low surface brightnesses >30 V-band mag/arcsec 2 . Recent deep diffuse light imaging has permitted detection of relatively massive halos (e.g., [34][35][36]). In parallel, studies of resolved red giant branch (RGB) stars in the outskirts of nearby galaxies reach fainter equivalent surface brightness limits and give estimates of both stellar halo masses and typical metallicities [7,8,[37][38][39][40][41].…”
Section: Stellar Halos Measure Merger Historymentioning
confidence: 99%
“…Since they are relatively shallow and have a small field of view, these studies are limited to the inner regions of nearby ETGs. However, deep optical imaging, together with the kinematics of planetary nebulae and of globular clusters, have revealed that these discs can extend much ⋆ E-mail: mkyildiz@astro.rug.nl further out (Romanowsky et al 2003;Pota et al 2013;Duc et al 2014Duc et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…They represent the region where the transition between galaxy halo and ICL can be traced. Moreover, as dynamical scales are longer, they preserve fossil records of accretion events imprinted in the star formation history and chemical enrichment, and revealed in the form of spatially extended low surface-brightness features [7,8]. These substructures are not phase-mixed in the host galaxy potential and, therefore, can also be traced as kinematic features in the velocity phase-space [9].…”
Section: Introductionmentioning
confidence: 92%